Jets and heavy flavour at LHC with ATLAS and CMS - Magnan,AM (2010)
The LHC experiments ATLAS and CMS plan to take advantage of large multi-jet samples with and without heavy flavour tagging and vector boson production to test QCD at the TeV scale. Initial multi-jet cross section measurements at LHC will demonstrate the understanding of the calibration of the detectors, the jet energy scale systematics and the trigger. Further in the LHC run, measurements of inclusive di-jet cross sections with heavy flavour tag, which provides the process hard scale, will probe QCD at scales never tested before. Jet production measurements with associated W and Z bosons provide a separate test of QCD in different and complementary channels. Measurements of these processes are essential to demonstrate the understanding of major backgrounds to Higgs and SUSY channels, such as those of top-quark production or W+jet/Z+jet.